Obesity Inhibits Angiogenesis Through TWIST1-SLIT2 Signaling - Hunyenyiwa, Tendai; Hendee, Kathryn; Matus, Kienna; Kyi, Priscilla; Mammoto, Tadanori; Mammoto, Akiko (Frontiers in Cell and Developmental Biology, 2021)
Angiogenesis is required for functional adipose tissue maintenance, remodeling, and expansion. Physiologically balanced adipogenesis and angiogenesis are inhibited in subcutaneous adipose tissue in obese humans. However, the mechanism by which angiogenesis is inhibited in obese adipose tissue is not fully understood. Transcription factor TWIST1 controls angiogenesis and vascular function. TWIST1 expression is lower in obese human adipose tissues. Here, we have demonstrated that angiogenesis is inhibited in endothelial cells (ECs) isolated from adipose tissues of obese humans through TWIST1-SLIT2 signaling. The levels of TWIST1 and SLIT2 are lower in ECs isolated from obese human adipose tissues compared to those from lean tissues. Knockdown of TWIST1 in lean human adipose ECs decreases, while overexpression of TWIST1 in obese adipose ECs restores SLIT2 expression. DNA synthesis and cell migration are inhibited in obese adipose ECs and the effects are restored by TWIST1 overexpression. Obese adipose ECs also inhibit blood vessel formation in the gel subcutaneously implanted in mice, while these effects are restored when gels are mixed with SLIT2 or supplemented with ECs overexpressing TWIST1. These findings suggest that obesity impairs adipose tissue angiogenesis through TWIST1-SLIT2 signaling.